Topical issues of digitalization of education in modern conditions - Elena Alexandrovna Panina (Вестник Майкопского государственного технологического университета)
The socio-cultural situation of the modern world is characterized by the active use of digital technologies in all spheres of life: economy, healthcare, services, education. The forced regime of restrictive measures during the coronavirus pandemic in the spring of 2020 changed the educational situation in the world directly, all educational institutions transitted totally to a distance format with the active use of digital educational environment. The implementation of digital education has contributed to changes not only in educational technologies, but also in its paradigm, the dominant component of which was digitalization - the process of transforming education into an electronic format. The research problem lies in the analysis of the category “digitalization of education”, identification of its content and principles. The purpose of the study is to reveal topical issues of digitalization of education in modern conditions. The research methodology consisted of a set of methods of scientific knowledge: analysis, synthesis, generalization. The research results are theoretical substantiation of the category “digitalization of education”; identification of the purpose and principles of digitalization of education in modern conditions; presentation of popular online training platforms that are used in the practice of higher educational institutions; formulation of the prospects for digitalization of education in modern conditions. Key conclusions: the digital educational environment includes meaningful and target contexts, integrating the progressive achievements of electronic educational technologies to ensure the development of educational programs by students in full, regardless of their location in accordance with the requirements of the legislation of the Russian Federation in the field of education in a distance format; distance education is carried out on the basis of popular online training platforms (Moodle, Edmodo, iSpring, WebTutor).